Congenital ataxia due to novel variant in ATP8A2. Issue 1 (22nd April 2021) - Damásio, Joana; Santos, Diana; Morais, Sara; Brás, José; Guerreiro, Rita; Sardoeira, Ana; Cavaco, Sara; Carrilho, Inês; Barbot, Clara; Barros, José; Sequeiros, Jorge
Abstract: Congenital ataxias are a heterogeneous group of disorders characterized by congenital or early‐onset ataxia. Here, we describe two siblings with congenital ataxia, who acquired independent gait by age 4 years. After 16 years of follow‐up they presented near normal cognition, cerebellar ataxia, mild pyramidal signs, and dystonia. On exome sequencing, a novel homozygous variant (c.1580‐18C > G ‐ intron 17) in ATP8A2 was identified. A new acceptor splice site was predicted by bioinformatics tools, and functionally characterized through a minigene assay. Minigene constructs were generated by PCR‐amplification of genomic sequences surrounding the variant of interest and cloning into the pCMVdi vector. Altered splicing was evaluated by expressing these constructs in HEK293T cells. The construct with the c.1580‐18C > G homozygous variant produced an aberrant transcript, leading to retention of 17 bp of intron 17, by the use of an alternative acceptor splice site, resulting in a premature stop codon by insertion of four amino acids. These results allowed us to establish this as a disease‐causing variant and expand ATP8A2 ‐related disorders to include less severe forms of congenital ataxia. Abstract :